Eclecticism as a philosophical mindset - Węcławski, Michał (Hybris, 2018)
The aim of this paper is to explore some of the meanings of frequently underestimated and misunderstood topic of eclecticism. In doing so, we would like to ask how the phenomenon of eclecticism was perceived in the past and whether it is correct to regard it as something more than just an abstract notion, namely: as a philosophical mindset and particular approach to life in general. The text is divided into two parts. The first one contains an outline of the history of eclecticism, understood as a notion and a kind of attitude. It is shown that, among others, it was thanks to the eclectic approach that emerging Christian civilisation would open itself to the heritage of the classical era; late antiquity and the Renaissance, both having produced ideas of religious humanism, are also indicated as the most eclecticism-related epochs. The second part aims at describing the phenomenon of eclecticism as, unlike syncretism, depending on a selection of elements rather than combining them together. It is presented as a way of philosophising and thus as a way of being, potentially creative and open to different viewpoints, yet, unlike skepticism, committed to the truth. All in all, the paper shall be perceived as a praise of eclecticism, assuming that it deserves far more appreciation and scholarly attention than has been given to it thus far.